2022
DOI: 10.1111/bpa.13115
|View full text |Cite
|
Sign up to set email alerts
|

Different modes of synaptic and extrasynaptic NMDA receptor alteration in the hippocampus of P301S tau transgenic mice

Abstract: N‐methyl‐d‐aspartate receptors (NMDARs) are pivotal players in the synaptic transmission and synaptic plasticity underlying learning and memory. Accordingly, dysfunction of NMDARs has been implicated in the pathophysiology of Alzheimer disease (AD). Here, we used histoblot and sodium dodecylsulphate‐digested freeze‐fracture replica labelling (SDS‐FRL) techniques to investigate the expression and subcellular localisation of GluN1, the obligatory subunit of NMDARs, in the hippocampus of P301S mice. Histoblots sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Additionally, accumulation of presynaptic Tau, amyloid-beta oligomers, impaired inhibitory interneuron and glial function or genetic risk factors may contribute to synaptic dysfunction in Alzheimer’s disease 3 . Notably, however, Tau reduction strongly reduces hyperexcitability in AD mouse lines, induced seizure models, and genetic in vivo models of epilepsy 51 , suggesting a critical role of Tau in synaptic dysfunction. Consistent with this hypothesis, clearance of postsynaptic Tau improved cognition in a tauopathy mouse model 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, accumulation of presynaptic Tau, amyloid-beta oligomers, impaired inhibitory interneuron and glial function or genetic risk factors may contribute to synaptic dysfunction in Alzheimer’s disease 3 . Notably, however, Tau reduction strongly reduces hyperexcitability in AD mouse lines, induced seizure models, and genetic in vivo models of epilepsy 51 , suggesting a critical role of Tau in synaptic dysfunction. Consistent with this hypothesis, clearance of postsynaptic Tau improved cognition in a tauopathy mouse model 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that tau is required for the function of extrasynaptic NMDARs [ 64 ] and that they are mostly increased in P301S mice [ 65 ]. In this study, we identified a reduction in both synaptic and extrasynaptic AMPARs in tau pathology in the two main neuronal populations of the CA1 field: pyramidal cells and interneurons.…”
Section: Discussionmentioning
confidence: 99%